Review of the Global Solar UV Index 2015 Workshop Report. Issue 1 (January 2018) - Gies, Peter; van Deventer, Emilie; Green, Adèle C.; Sinclair, Craig; Tinker, Rick
Abstract : Abstract: The Global Solar UV Index was developed as an easy-to-understand measure of the amount of biologically-effective ambient solar ultraviolet radiation (UVR) at different locations on the earth's surface. Over the past few years, questions have been raised about the global applicability of the UV Index, about the evidence base for exposure risk thresholds and related protective measures, and about whether the overall impact of the UV Index could be improved with modifications. An international workshop was organized by several organizations, including the World Health Organization, to assess if current evidence was sufficiently strong to modify the UV Index and to discuss different ways it might be improved in order to influence sun-protective behavior. While some animal research suggests there may be no threshold effect, the relative importance of sub-erythemal doses of sunlight in causing skin cancer in humans remains unknown. Evidence suggests that regular use of sunscreen can prevent skin cancer and that sunglasses are an effective method of protecting the eyes from solar UVR. The UV Index as a risk communication tool continues to be useful for raising awareness and to support sun-protection behavior. Although there was agreement that guidance on the use of the UV Index could be improved, the workshop participants identified that strong health outcome-based human evidence would be needed as the basis for a revision. For the UV Index to be relevant in as many countries as possible, it should continue to be adapted to suit local conditions.